Biological Soil Crust Response to Late Season Prescribed Fire in a Great Basin Juniper Woodland - Warren, Steven D.; St.Clair, Larry L.; Johansen, Jeffrey R.; Kugrens, Paul; Baggett, L. Scott; Bird, Benjamin J. (Rangeland ecology & management, 2015)
Expansion of juniper on U.S. rangelands is a significant environmental concern. Prescribed fire is often recommended to control juniper. To that end, a prescribed burn was conducted in a Great Basin juniper woodland. Conditions were suboptimal; fire did not encroach into mid- or late-seral stages and was patchy in the early-seral stage. This study evaluated the effects of the burn on biological soil crusts of early-seral juniper. Fire reduced moss cover under sagebrush and in shrub interspaces. Mosses were rare under juniper; their cover was unaffected there. Lichens were uncommon under juniper and sagebrush and therefore not significantly impacted there. Their cover was greater in shrub interspaces, but because the fire was spotty and of low intensity, the effects of burning were minimal. Compared with unburned plots, the biomass of cyanobacteria was diminished under juniper and sagebrush; it was reduced in the interspaces in both burned and unburned plots, presumably in response to generally harsher conditions in the postburn environment. Nitrogen fixation rates declined over time in juniper plots and interspaces but not in sagebrush plots. Although fire negatively affected some biological soil crust organisms in some parts of the early-seral juniper woodland, the overall impact on the crusts was minimal. If the intent of burning is to reduce juniper, burning of early-seral juniper woodland is appropriate, as most affected trees were killed. Control of sagebrush can likewise be accomplished by low-intensity, cool season fires without eliminating the crust component. Intense fire should be avoided due to the potential for greater encroachment into the shrub interspaces, which contain the majority of biological soil crust organisms. Burning early-seral juniper may be preferred for controlling juniper encroachment on rangeland.